Single-Cell Characterization of Hepatic CD8+ T Cells in a Murine Model of Primary Biliary Cholangitis - Han, Yichen; Bian, Zhen-Hua; Yang, Si-Yu; Wang, Cheng-Bo; Li, Liang; Yang, Yan-Qing; Ansari, Aftab A.; Gershwin, M. Eric; Zeng, Xiaofeng; Lian, Zhe-Xiong; Zhao, Zhi-Bin (Frontiers in Immunology, 2022)
Primary biliary cholangitis (PBC), an organ-specific autoimmune disease, is characterized by injury to small bile ducts, inflammatory cell infiltrates within the liver, progressive cholestasis, and in some cases, cirrhosis with unclear pathogenesis. We aimed to clarify the importance role of hepatic immunce cells in the pathogenesis of human and experimental PBC.The dominant-negative TGFβ receptor type II transgenic (dnTGFβRII) mice, a well-studied and established murine model of PBC were used to identify changes of immune cells, especially the pathogenic CD8+ T cells. The high-throughput single-cell RNA sequencing technology were applied and found functional heterogeneity among the hepatic CD8+ T cells subsets in dnTGFβRII mice. CD8+ T cells were confirmed the key cells leading to the pathogenesis of PBC in dnTGFβRII mice, and identified the terminally differentiated CD8αα T cells and CD8αβ T cell subsets in the liver of dnTGFβRII mice. While terminally differentiated CD8αα T cells have higher cytokine production ability and cytotoxicity, the terminally differentiated CD8αβ T cells retain their proliferative profile. Our work suggests that there are developmental and differentiated trajectories of pathogenic CD8+ T cell subsets in the pathogenesis of PBC. A further clarification of their roles would be helpful to our understanding of the pathogenesis of PBC and may potentially lead to identifying novel therapeutic modalities.